This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Althought tan ( y + z ) = 1 − tan y ⋅ tan z tan y + tan z = tan x , it depends on which cuadrants the angles belongs to. Take y = tan − 1 ( 2 1 ) , z = tan − 1 ( 3 1 ) belonging to the first cuadrant, then 0 < y < 4 5 º , 0 < z < 4 5 º ⇒ 0 < y + z < 9 0 º and take x = 2 2 5 º